10.61533 ACTIVITY BASED COSTING METHOD SEBAGAI ALTERNATIF PENENTUAN HARGA POKOK TARIF JASA RAWAT INAP PADA RSUD DEPATI HAMZAH KOTA PANGKALPINANG - Jessica, Nella; Novika; Maharani, Yunita (Jurnal Ilmiah Niaga Bisnis Elektronik, 2024)
The techniques used in data collection were interviews, literature study, documentation, and internet search. The data analysis technique used was qualitative with descriptive comparative apporach. The research results indicate that: (1) the calculation of inpatient rates using the mehod applied by RSUD Depati Hamzah Kota Pangkalpinang is carried out by charging facility fees per days of treatment, service fees per length of treatment, and reduction per day if the doctor does not visit, while the calculation of inpatient rates using the Activity Based Costing Method is carried out by charging activities that are the patient’s responsibility, such as doctor fees, laundry, consumption, telephone, electricity and water, security, administration, and cleanliness; (2) the inpatiient rates used by RSUD Depati Hamzah Kota Pangkalpinang are higher for VIP Class compared to the Activity Based Costing Method, while for Classes I-III, the hospital rates are lower; (3) the Activity Based Costing Method cannot yet be applied at RSUD Depati Hamza Kota Pangkalpinag due to the lack of consideration related to the continuity and development of services, community purchasing power, principles of justice and propriety, and healthy competition.